Molecular Phylogeny of Cryptonanus (Didelphidae: Thylamyini): Evidence for a recent and complex diversification in South American open biomes - Fegies, Ana Cláudia [UNESP]; Carmignotto, Ana Paula; Perez, Manolo Fernandez; Guilardi, Mariana Dias; Lessinger, Ana Cláudia (Elsevier, 2021)
Systematic revisions of South American marsupials have contributed to our knowledge about genus and species diversity in the last decades, including studies of the most recently described genus Cryptonanus (Didelphidae), currently comprising four recognized species. Herein we provide the first phylogeny for these mouse opossums based on comprehensive sampling, including representatives from all nominal taxa, encompassing most of the geographic distribution of the genus while also extending its known range. The taxonomic status of Cryptonanus species was explored by analyses of multiple mitochondrial and nuclear DNA markers to assess phylogenetic relationships and to provide divergence time estimates, species delimitations and biogeographical hypotheses. Cryptonanus monophyly remained highly supported despite the inclusion of abundant new data from more than a hundred specimens, comprising 10 independent evolutionary lineages. Species-complexes within valid nominal taxa reveal higher species richness in the genus. Based on divergence estimates from a dated phylogeny, we suggest that Cryptonanus diversified along the Quaternary, with speciation events occurring well into the Pleistocene. The best supported biogeographical hypothesis endorses speciation by vicariance and subset speciation across open formations in shaping the evolutionary history of this didelphid genus, strongly associated with dry tropical landscapes of South America.
Keywords: Biogeography; Diversification; Marsupial; Neotropics; Species delimitation; Systematics